567 Wolff–Parkinson–White syndrome and sport activity: a peculiar case in a young athlete. (8th December 2021) - Licciardello, Claudio; Golino, Michele; Seganfreddo, Francesca; Matteo, Federica; Giovenzana, Fulvio Lorenzo Francesco; Franzosi, Cinzia; Genoni, Paola; Marazzato, Jacopo; De Ponti, Roberto
Abstract: Aims: Wolff–Parkinson–White (WPW) is a cardiac conduction system disorder characterized by abnormal accessory conduction pathways between the atria and the ventricles. Palpitations, presyncope, or syncope that result from supraventricular tachycardia represent classic symptoms; however, especially in young athletes, the syndrome can occur with sudden cardiac death. As result, the presence of an accessory pathway (AP) and tachycardia induced by physical activity contraindicates agonist physical activity and represents an indication to perform an electrophysiology (EP) study to stratify the arrhythmic risk, also allowing an eventual transcatheter ablation (TCA) of the AP. Methods and results: An agonist football player, known since the age of 6 years for Wolff–Parkinson–White syndrome from an intermittent right midseptal parahissian AP, underwent a transesophageal EP study and subsequently ineffective TCA with radiofrequency when he was 13 years old. For evidence of intermittent ventricular preexcitation (VPE), at the age of 15 he underwent a further endocavitary EP study with documentation of poor conductive abilities of the AP. Subsequently, at the age of 17, he had a resumption of palpitation and lipotimie during effort; during another sport medical examination with an exercise stress test (EST), a persistent VPE with the start of an orthodromic atrioventricular reentrant tachycardia during the recovery phase was documented. A new EP study with isoprenaline infusion confermed the precence of the parahissian AP and the inducibility of an orthodromic atrioventricular reentrant tachycardia (Picture 1-2B) ; therefore, after mapping the arrhythmia, a cryoablation of AP was performed (Picture 1c-1d). Nevertheless, 12 h after the procedure, there was still evidence of intermittent VPE. The patient was then discharged and, after a month, he repeated the EST with documentation of persistent VPE which suddenly disappeared at the peak of the exercise and reappeared during the recovery phase. At the 1-year follow-up, no arrhythmic recurrence but persistence of VPE was reported and a successive EST confirmed abrupt interruption of VPE at the peak of the exercise. Due to the low arrhythmic risk, sport activity was not more restricted. Conclusions: This represents an original clinical case, as it raises the question of what practical criteria should be defined as an effective TCA of AP in a competitive athlete with unfavorable anatomy. The current guidelines (Sport Cardiology and Exercise 2020) provide useful indications in linear and common cases, but may be a source of doubts in particular cases. Therefore, only the experience and the careful evaluation of the individual patient can provide the key to a correct management of the cases like this.